Soluble transferrin receptor and zinc protoporphyrin - competitors or efficient partners? - Metzgeroth, Georgia; Adelberger, Verena; Dorn-Beineke, Alexandra; Kuhn, Christian; Schatz, Michael; Maywald, Ole; Bertsch, Thomas; Wisser, Hermann; Hehlmann, Rüdiger; Hastka, Jan (European journal of haematology, 2005)
Objectives: Soluble transferrin receptor (sTfR) and zinc protoporphyrin (ZPP) are both parameters of iron deficient erythropoiesis (IDE), the sTfR measurement is commonly regarded to be the more sensitive test. sTfR also reflects erythropoietic activity, it is increased in enhanced erythropoiesis. Methods: We investigated the diagnostic accuracy of sTfR in assessment of iron deficiency (ID) and compared it with ZPP. The study was performed on 174 subjects, in which ID has been precisely staged. Results: Individuals without ID and patients with storage iron depletion only, had normal sTfR values. Patients classified as IDE and patients with iron deficiency anemia had significantly increased sTfR. There was a good correlation between sTfR and hemoglobin (r = −0.86; P < 0.0001) and between sTfR and ZPP (r = 0.86; P < 0.0001). When diagnosing ID, ZPP was the more sensitive test. In mildly developed IDE associated with ZPP-ratios between 40 and 70 μmol/mol heme, the sTfR concentration was elevated in only 25% of the cases. Reliably elevated sTfR values were observed only in more advanced IDE, associated with ZPP > 70 μmol/mol heme. Conclusions: ZPP is not inferior to sTfR when diagnosing IDE. Given the good correlation between sTfR and ZPP and because ZPP is uninfluenced by the erythropoietic activity, sTfR and ZPP are not competitors, rather efficient partners in diagnosing anemias. By measuring ZPP and sTfR simultaneously, the diagnostic uncertainty inherent in each of them individually can be eliminated. In particular, the simultaneous determination of ZPP and sTfR enhances the diagnostic power of sTfR in assessment of the erythropoietic activity.